Did advice on the prescription of sodium valproate reduce prescriptions to women? An observational study in three European countries between 2007 and 2016. Issue 11 (26th August 2019) - Charlton, Rachel; Damase‐Michel, Christine; Hurault‐Delarue, Caroline; Gini, Rosa; Loane, Maria; Pierini, Anna; Puccini, Aurora; Neville, Amanda; Snowball, Julia; Morris, Joan K.; ,
Abstract: Objectives: In November 2014, the CMDh (a regulatory body representing EU Member States) advised doctors not to prescribe sodium valproate for epilepsy or bipolar disorder in preg nant women, in women who can become pregnant, or in girls unless other treatments are ineffective or not tolerated. This study aimed to determine if this warning led to changes in prescription patterns. Design and setting: Cohort of 5.4 million women aged between 10 and 50 years identified in electronic health care data from United Kingdom, France, and Italy (2007–2016). Main outcome measures: Anti‐epileptic drug (AED) prescriptions. Results: The prevalence of women receiving AED prescriptions in 2016 varied from 12.2 per 1000 to 29 per 1000 in the four regions. The incidence of prescribing any AED (excluding clonazepam, gabapentin, and pregabalin) fell each year on average by 7.5% (95% CI, 7.0%‐8.0%; Emilia Romagna), 9.6% (8.3%‐11.0%; France), 7.1% (6.7%‐7.6%; Tuscany), and 0.4% (0.2%‐1.0%; United Kingdom). The relative odds of prescribing sodium valproate rather than any other AED decreased more after 2014 compared with before the end of 2014 in France (OR = 0.77; 95% CI, 0.60‐0.98), Tuscany (0.81; 0.76‐0.86), Emilia Romagna (0.83; 0.76‐0.90), and the United Kingdom (0.92; 0.80‐1.06; not statistically significant). Conclusions: There is evidence that the CMDh warning did lead to changes in prescription patterns of sodium valproate in women of childbearing age. There were considerable differences in prescribing practice amongst regions of Europe.